(untitled) (Journal of Science and Technology, 2016)
Quality assurance is essential to any programme of diagnostic radiology, to prevent undue exposure of x-ray personnel and patients to radiation. This paper reports observations from a survey of some hospital x-ray facilities in Accra and Kumasi in Ghana, to find out about steps taken by x-ray workers to ensure quality control and administration in diagnostic radiology. The grid point method has been used to do a detailed study of scatter radiation levels of two x-ray departments in Accra. The iso-dose rate contours have been analysea, and results show the importance of good design of x-ray rooms and provision of protective structures.